Exploring the Impact of the STAD Cooperative Learning Model on Learning Outcomes in Vocational High Schools - Wila Mutiara Yeni; Ilmiyati Rahmy Jasril; Sartika Anori; Kenan Işık; Xue Wan (Sagamedia Teknologi Nusantara, 2023)
This study examines the impact of the Student Team Achievement Division (STAD) cooperative learning model on student learning outcomes in technical education, specifically focusing on